North Korean climate diplomacy: engagement, priorities, and opportunities for collaboration - Scartozzi, Cesare M. (2024)
This study investigates North Korea’s climate diplomacy by analyzing a comprehensive dataset of 39 policy documents and 93,439 news articles through content and sentiment analysis. The research aims to provide insights into the country’s climate diplomacy approach, framing, and priorities. The findings reveal that North Korea’s climate diplomacy is primarily driven by materialistic interests, focusing on loss and damage reduction, access to climate finance, and technology transfers. The study highlights key themes in North Korea’s climate change discourse, such as economic factors, human security, and a surprisingly non-ideological stance. The sentiment analysis also indicates a collaborative approach toward the international community and strong support for UNFCCC mechanisms. The results offer valuable and nuanced implications for future diplomatic efforts, suggesting potential avenues for collaboration and engagement with North Korea on climate change issues. Nonetheless, the study also identifies several barriers to diplomatic engagement, such as North Korea’s reluctance to accept certain conditionalities associated with climate finance as well as its contentious focus on nuclear energy as a climate mitigation instrument. Overall, this research contributes to the growing literature on climate diplomacy and sheds new light on an underexplored aspect of North Korea’s foreign policy.